UJI DAYA HAMBAT LOTION EKSTRAK KULIT NANAS (Ananas comosus L.) DENGAN VARIASI KONSENTRASI ASAM STEARAT DAN TRIETANOLAMIN TERHADAP Staphylococcus aureus - yusriyani burhamin; Syarifuddin KA; Sutriana (Akademi Farmasi Yamasi Makassar, 2026)
Pineapple peel contains secondary metabolites in the form of flavonoids, saponins, and tannins. These metabolite compounds have antibacterial activity against Staphylococcus aureus. These compounds were obtained by maceration using 96% ethanol The extract obtained was then made into a lotion preparation. This study was conducted to determine the effect of varying concentrations of stearate acid and triethanolamine as emulgators of pineapple fruit peel extract lotion preparations (Ananas comosus L.) in inhibiting the growth of Staphylococcus aureus bacteria. The concentration of extract for each formula is 5%. Variation of stearic acid and triethanolain concentrations for formula I (5%; 4%), formula II (5.5%; 3.5%) and formula III (6%; 3%). The results showed that formula I, formula II and formula III had inhibition diameters that were not much different with inhibition zones of 10.21 mm, 9.72 mm and 10.13 mm respectively. Based on the results of the study, it can be concluded that variations in the concentration of stearic acid and triethanolamine in pineapple peel extract lotion preparations (Ananas comosus L.) have no effect on the inhibition of staphylococcus aureus bacteria.